The Lakewood boys in the frozen North - Wyman, L. P. (Levi Parker), 1873-1950 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Lakewood Boys in the Frozen North" by L. P. Wyman is a fiction novel likely written in the early 20th century. The story follows brothers Bob and Jack Lakewood, who embark on an adventurous quest in the frozen landscapes of Alaska. In this thrilling tale, they face numerous challenges, including a shipwreck and encounters with wildlife, showcasing their bravery and resourcefulness. At the start of the narrative, the Lakewood brothers are aboard a ship that encounters disaster after possibly striking an iceberg. As chaos erupts on board, they exhibit their courage and quick thinking by helping others into lifeboats and ultimately saving their captain from unconsciousness. After narrowly escaping the sinking ship, they find themselves on a journey through harsh conditions, illustrating both the physical demands of their environment and their determination to continue their exploration in search of their missing uncle in the Yukon Territory. With the aid of their guide, a Native American known as Lucky, they navigate the treacherous terrain, face the threat of wolves, and overcome various challenges as they delve deeper into the frozen wilderness. (This is an automatically generated summary.)
Release date is 2024-07-15
Al Haines
Keywords: Adventure stories; Brothers -- Juvenile fiction; Alaska -- Juvenile fiction